Implementasi Psikologi Manajemen dalam Pendidikan untuk Meningkatkan Kinerja Mutu Pembelajaran dan Lingkungan Kerja Kondusif - Anggun Amelia Contessa; Moelyaning Siwi; Mualimin Mualimin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Management psychology in education has become a crucial issue with the growing need for effective learning management that focuses on individual behavior. This approach focuses not only on the technical aspects of management but also on understanding the psychology of students and educators. This study aims to examine the role of management psychology in improving learning effectiveness and the performance of educational organizations, as well as answering the research question of how the implementation of management psychology contributes to educational quality. The method used was a qualitative literature review using the Google Scholar and Publish or Perish databases with the keyword